2019
DOI: 10.14444/6002
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Range of Motion and Stress Patterns at the Transitional Lumbosacral Junction: Pilot Study Using a Computational Model for Load-Bearing at Accessory L5-S1 Articulation

Abstract: Background: Symptomatic or asymptomatic transitional anomalies at the lumbosacral junction are common occurrences in the population. Lumbosacral (L5-S1) accessory articulations are the most common presentations of transitional anomalies at this region. Such anatomical alterations are believed to be associated with biomechanical changes of load-bearing and movement restrictions leading to low back pain. This study attempts to use computational models of a normal and a lumbosacral transitional vertebrae (LSTV) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…The range of motion obtained in numerical simulations was compared with the one reported in previously published experimental and numerical studies ( Yamamoto et al, 1989 ; Tullberg et al, 1998 ; Ivanov et al, 2009 ; Jahng et al, 2013 ; Dreischarf et al, 2014 ; Kyaw et al, 2014 ; Lindsey et al, 2015 ; Nagamoto et al, 2015 ; Coombs et al, 2017 ; Jaramillo and Garcia, 2017 ; Kibsgård et al, 2017 ; Joukar et al, 2018 ; Mahato et al, 2019 ; Supplementary Figures 1 , 4 ).…”
Section: Methodsmentioning
confidence: 86%
See 1 more Smart Citation
“…The range of motion obtained in numerical simulations was compared with the one reported in previously published experimental and numerical studies ( Yamamoto et al, 1989 ; Tullberg et al, 1998 ; Ivanov et al, 2009 ; Jahng et al, 2013 ; Dreischarf et al, 2014 ; Kyaw et al, 2014 ; Lindsey et al, 2015 ; Nagamoto et al, 2015 ; Coombs et al, 2017 ; Jaramillo and Garcia, 2017 ; Kibsgård et al, 2017 ; Joukar et al, 2018 ; Mahato et al, 2019 ; Supplementary Figures 1 , 4 ).…”
Section: Methodsmentioning
confidence: 86%
“…We compared the range of motions (ROMs) of our finite element model for each movement with the ones reported on the basis of experimental or numerical studies by Yamamoto et al (1989) ; Hungerford et al (2004) , Ivanov et al (2009) ; Dreischarf et al (2014) , Kyaw et al (2014) ; Lindsey et al (2015) , Nagamoto et al (2015) ; Coombs et al (2017) , Hu et al (2017) ; Jaramillo and Garcia (2017) , Kibsgård et al (2017); Cross et al (2018) , Joukar et al (2018) , and Mahato et al (2019) (ROM for L4/L5 and L5/S1: Supplementary Figure 1 ; ROM for SI: Supplementary Figure 4 ). In the L4/L5 movement (vector ), and L5/S1 movement (vector ), our model was in excellent agreement with the literature for flexion and lateral bending, while showed slightly higher values for axial rotation ( Supplementary Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…They further reported that patients with FAI required more flexion at the hip to achieve the sitting position because of their inability to compensate through the lumbar spine. 16,17 Lumbar motion is critical to this compensatory mechanism; however, as shown by Mahato et al, 30 loss of motion at the transitional segments is one of the consequences of LSTV. On this basis, we speculate that our study's outcomes for patients with LSTV are attributed to an impairment of the lumbar spine that contributes to the compensatory changes in pelvic sagittal alignment, 25 thus resulting in increased FAI or residual FAI after HA.…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with biomechanical and finite element studies that show that even with more stiffness, low-grade transitional vertebrae do retain some degree of mobility that may not be present in those with fused vertebrae. 19,20 Future investigations can certainly evaluate whether these patients with more fusion, hence less lumbosacral motion, indeed perform more poorly following hip arthroscopy.…”
Section: See Related Article On Page 149mentioning
confidence: 99%